Microbiological and chemical characterization of Cabacinha cheese marketed in three municipalities in Vale do Jequitinhonha (Research, Society and Development, 2020)
Cabacinha cheese from Vale do Jequitinhonha is similar mozzarella, but in this milk is crude, being the product is stored at ambient without packaging. Besides it contributes to local income, customers may be food-poisoned. The objective of this study was to verify the physical-chemical and microbiological characteristics of samples of Cabacinha cheese produced and marketed in Vale do Jequitinhonha-MG. Samples were bought in tents (n=25), restaurants (n=4) and bakeries (n=2) located by BR 251 and BR 116 highways in the towns of Medina, Cachoeira de Pajeú and Pedra Azul. Cheeses from 17 marketplaces were purchased from the first town, 10 from the second and 4 from the third, respectively. The coliforms at 35ºC, Escherichia coli, coagulase positive Staphylococcus, lactic acid bacteria, filamentous fungi and yeasts were 1.8 x 103; 1 x 101; 4.6 x 103; 6.3 x 107 and 4.9 x 106 Colony Forming Units per gram, respectively, and Salmonella spp. are absent. The chemical characteristics mean was 26.47% of protein, 27.69% of fat, 4.34% of minerals, 36.23% of moisture, 843.66 mg/100g of sodium and pH of 5.14. This is the first paper that describes microbiological and chemical characteristics of Cabacinha cheese from Vale do Jequitinhonha. The absence of regulations for microbiological parameters may put the health of consumers at risk.